2023
DOI: 10.3390/polym15071701
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Production of Biomaterials through Kombucha Using Food Waste: Concepts, Challenges, and Potential

Abstract: In recent years, several researchers have focused their studies on the development of sustainable biomaterials using renewable sources, including the incorporation of living biological systems. One of the best biomaterials is bacterial cellulose (BC). There are several ways to produce BC, from using a pure strain to producing the fermented drink kombucha, which has a symbiotic culture of bacteria and yeasts (SCOBY). Studies have shown that the use of agricultural waste can be a low-cost and sustainable way to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The consortia have a high adaptive potential, and the coordinated consumption of a substrate and the formation of metabolites enhance their tolerance to nutrient media of a variable composition and increase the target product (BNC) yield, which is of special importance in a real production setting [ 45 , 46 ]. Therefore, the whole trend of using the symbiotic culture for BNC biosynthesis has emerged in the literature worldwide in the recent times [ 33 , 38 , 39 , 41 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consortia have a high adaptive potential, and the coordinated consumption of a substrate and the formation of metabolites enhance their tolerance to nutrient media of a variable composition and increase the target product (BNC) yield, which is of special importance in a real production setting [ 45 , 46 ]. Therefore, the whole trend of using the symbiotic culture for BNC biosynthesis has emerged in the literature worldwide in the recent times [ 33 , 38 , 39 , 41 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…BC is an attractive biopolymer for a number of applications including food, biomedical, cosmetics, and engineering fields. The review by Cubas et al (2023) reported BC to be a new era in Green Chemistry products [ 165 ]. In the past five years, there have been many interesting, detailed reviews describing BC production, properties, and applications [ 43 , 65 , 68 , 71 , 72 , 73 , 74 , 76 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ].…”
Section: Bacterial Cellulose-producing Bacteriamentioning
confidence: 99%
“…BC has great potential to be used in medicine [ 2 , 3 , 43 , 71 , 72 , 73 , 74 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 179 ] as a biomaterial for wound dressing [ 180 , 181 , 182 , 183 , 184 , 185 , 186 ], tissue engineering [ 187 , 188 , 189 , 190 , 191 , 192 ], and drug delivery systems [ 51 , 193 , 194 , 195 , 196 , 197 ]. In addition, BC can be used in the food industry as a nutritional component, food packaging, an emulsion stabilizer, and novel food [ 165 , 198 , 199 , 200 ]. BC is known as a fiber-rich natural food that offers many health benefits and reduces the risk of chronic diseases, such as diabetes, obesity, and cardiovascular diseases [ 199 ].…”
Section: Bacterial Cellulose-producing Bacteriamentioning
confidence: 99%
“…One of the most widespread high-performance technologies for producing BNC is based on fermentation with a symbiotic culture of Medusomyces gisevii, known under such traditional names as "Nata" or "Kombucha" and which has a long tradition of food use [14]. BNC obtained by this method has very high content of cellulose allomorph Iα (CIα) in the range of 94-100% and degree of crystallinity (CI) in the range of 88-93%, which will give it high functional characteristics, making it an attractive substance for food use.…”
Section: Introductionmentioning
confidence: 99%